Disparities in Obstetrical Outcomes in ART Pregnancies Compared with Natural Conceptions - Plowden, Torie C.; Novak, Christopher M.; Spong, Catherine Y. (Seminars in Reproductive Medicine, 2013)
Health disparities are observed in all fields of medicine and reproductive health is not immune to this phenomenon. The incidence of women using infertility treatments to conceive is increasing. Women undergoing assisted reproduction appear to be at increased risk of adverse outcomes, and minority women tend to be at even greater risk. This article examines several adverse obstetrical outcomes including preterm birth, congenital malformations, and preeclampsia among women receiving infertility treatments compared with those who conceive spontaneously. It will further examine societal costs associated with these procedures.
Keywords: assisted reproduction; spontaneous conception; ethnic disparities